2022
DOI: 10.1021/acs.jpclett.2c02499
|View full text |Cite
|
Sign up to set email alerts
|

Retardation of Capillary Force between Janus Particles at the Oil–Water Interface

Abstract: Interactions among colloidal particles govern the hierarchical microstructure and its physical properties. Here, optical laser tweezers and Monte Carlo simulations are used to evaluate the effects of azimuthal rotation of Janus particles at the oil–water interface on interparticle interactions. We find that the capillary-induced attractive force between two Janus particles at the interface can be relaxed by azimuthal rotation around the critical separation region, at which the capillary force is ∼0.053 pN. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Jeong et al [148] applied optical laser tweezers and Monte Carlo simulations to evaluate the effects of the azimuthal rotation of Janus particles at the oil-water interface on interparticle interactions. They found that the capillary-induced attractive force between two Janus particles at the interface can be relaxed by azimuthal rotation around the critical separation region.…”
Section: Spherical Janus Particlesmentioning
confidence: 99%
“…Jeong et al [148] applied optical laser tweezers and Monte Carlo simulations to evaluate the effects of the azimuthal rotation of Janus particles at the oil-water interface on interparticle interactions. They found that the capillary-induced attractive force between two Janus particles at the interface can be relaxed by azimuthal rotation around the critical separation region.…”
Section: Spherical Janus Particlesmentioning
confidence: 99%
“…Therefore, in a dilute regime (i.e., low particle surface coverage), when two particles approach each other in a favorable configuration (i.e., deformation modes are matching), attraction will be ensued. If the particles approach each other in a unfavorable configuration, assuming they are free to rotate in plane (radial movement on the graph), they can align their deformations and switch to the attraction region of the capillary interaction map 43,96 . For instance, in a system composed of two particles interacting via hexapolar capillary interactions, the maximum in‐plane rotation needed for a single particle to switch the interaction potential sign, and move from maximum repulsion to maximum attraction, is 60°.…”
Section: Resultsmentioning
confidence: 99%
“…If the particles approach each other in a unfavorable configuration, assuming they are free to rotate in plane (radial movement on the graph), they can align their deformations and switch to the attraction region of the capillary interaction map. 43,96 For instance, in a system composed of two particles interacting via hexapolar capillary interactions, the maximum in-plane rotation needed for a single particle to switch the interaction potential sign, and move from maximum repulsion to maximum attraction, is 60 . Figure 8B other in the most unfavorable orientation may need to rotate up to (180 ) to move from a repulsive domain toward an attractive range.…”
Section: Pairwise Capillary Interactionsmentioning
confidence: 99%
“…A flow cell was constructed with inner and outer cylinders, as previously reported [ 24 , 25 , 49 ]. Briefly, the inner hollow cylinder was a Teflon ring (9 mm in height and 12 mm in diameter) attached to the inside of an aluminum ring (8 mm in height and 14 mm in diameter).…”
Section: Methodsmentioning
confidence: 99%
“…After 30 min of stabilization, the particle–particle interaction was measured using optical laser tweezers (10 W CW Nd:YAG laser, λ = 1064 nm, Coherent Matrix, USA) connected with an inverted microscope (Ti-U, Nikon, Japan). The laser beam, passing through a water immersion objective lens (CFI Plan Apochromat VC 60, NA = 1.2, Nikon, Japan), was highly focused on a focal plane, resulting in an optical trap [ 25 , 47 , 49 ]. An acousto-optic deflector (Opto-electric DTSXY-400-1064, OPTO-ELECTRONIC, France) was used to generate multiple traps, and trap positions were individually controlled using the LabVIEW software.…”
Section: Methodsmentioning
confidence: 99%